Rapid and efficient one‐step purification of a serralysin family protease by using a p‐aminobenzamidine‐modified affinity medium. Issue 9 (18th April 2017) - Li, Shangyong; Wang, Linna; Lin, Shengxiang; Yang, Juan; Ma, Zibin; Wang, Yuejun; Liu, Junzhong; Hao, Jianhua; Sun, Mi
Abstract : The metalloproteinase MP belongs to the serralysin family, which is involved in important functions such as nutrient acquisition and infection pathogenesis. Serralysin proteases in highly purified form are commonly used at the industrial level with several purposes. In this study, we set up an efficient and rapid purification protocol for MP using a p ‐aminobenzamidine‐modified affinity chromatography. The affinity medium was synthesized by using p ‐aminobenzamidine as affinity ligand immobilized via cyanuric chloride spacer to Sepharose 6B sorbent carrier. According to the adsorption analysis, the dissociation constant K d and theoretical maximum adsorption Q max of this medium were 24.2 μg/mL and 24.1 mg/g wet sorbent, respectively. The purity of MP was assessed by a high‐performance liquid chromatography on a TSK3000SW column and sodium dodecyl sulfate polyacrylamide gel electrophoresis, revealing values of 98.7 and ∼98%, respectively. The specific activity of purified MP was 95.6 U/mg, which is similar to values obtained through traditional purification protocols. In conclusion, our protocol could be easily employed for the rapid isolation of MP with high purity, and could be implemented for other serralysin family proteases.